Synthesis of waste cooking oil-based polyurethane for solid polymer electrolyte - Salleh, W.N.F.W.; Tahir, Syuhada Mohd; Mohamed, Nor Sabirin (Springer Verlag (Germany), 2018)
Bio-based polyurethane (PU) was synthesized from waste cooking oil-based polyol for application as host in solid polymer electrolyte. The effect of varying wt% of lithium iodide (LiI) salt as charge carriers was studied. The polymer electrolyte films were characterized using Fourier transform infrared (FTIR), electrochemical impedance spectroscopy, scanning electron microscope (SEM), differential scanning calorimeter and thermogravimetric analysis. The shifting of absorption peaks for amine (N–H), carbonyl (C=O) and ether (C–O–C) groups observed in FTIR analysis showed that the PU-LiI complexation had occurred. The highest ionic conductivity obtained was at 30% LiI with value of 4.67 × 10−6 Scm−1. SEM revealed the good miscibility between lithium salt and PU. These properties exhibited the potential of waste cooking oil-based PU as alternative host for solid polymer electrolyte.